2003
DOI: 10.1128/jvi.77.17.9369-9377.2003
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization with Neutralizing Antibodies Interrupts the Mouse Mammary Tumor Virus Life Cycle

Abstract: Mouse mammary tumor virus (MMTV) infects the host via mucosal surfaces and exploits the host immune system for systemic spread and chronic infection. We have tested a neutralizing rat monoclonal antibody specific for the retroviral envelope glycoprotein gp52 for its efficiency in preventing acute and chronic mucosal and systemic infection. The antibody completely inhibits the superantigen response and chronic viral infection following systemic or nasal infection. Surprisingly however, the antibody only partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although premature at this stage of research, it is of interest that the development of preventive and therapeutic vaccines against MMTV in humans is a practical proposition. MMTV-associated mouse mammary tumors can be prevented from developing by immunization with purified mammary tumor virus ( 194 – 196 ). MMTV virus envelope peptides have also been used to prevent MMTV-associated mouse breast cancers ( 197 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although premature at this stage of research, it is of interest that the development of preventive and therapeutic vaccines against MMTV in humans is a practical proposition. MMTV-associated mouse mammary tumors can be prevented from developing by immunization with purified mammary tumor virus ( 194 – 196 ). MMTV virus envelope peptides have also been used to prevent MMTV-associated mouse breast cancers ( 197 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse mammary tumour virus: studies conducted several decades ago on experimental mice indicate the possibility of developing preventive vaccines [ 86 ]. More recently Braitbard et al working in Israel have shown the possibility of MMTV derived proteins used to prevent and treat MMTV breast infections [ 87 ].…”
Section: Preventionmentioning
confidence: 99%